N-terminal domain of PB1-F2 protein of influenza A virus can fold into amyloid-like oligomers and damage cholesterol and cardiolipid containing membranes - Ajjaji, Dalila (2016)
PB1-F2 protein is a factor of virulence of influenza A viruses which increases the mortality and morbidity associated with infection. Most seasonal H1N1 Influenza A viruses express nowadays a truncated version of PB1-F2. Here we show that truncation of PB1-F2 modified supramolecular organization of the protein in a membrane-mimicking environment. In addition, full-length PB1-F2(1–90) and C-terminal PB1-F2 domain (53–90), efficiently permeabilized various anionic liposomes while N-terminal domain PB1-F2(1–52) only lysed cholesterol and cardiolipin containing lipid bilayers. These findings suggest that the truncation of PB1-F2 may impact the pathogenicity of a given virus strain.